Catch-up Growth Based on International Talent Mobility in an Idea-Based World - QUAN, Yu (Institutional Knowledge at Singapore Management University, 2003)
We show how catch-up growth can result when immigrant ties of talented people to their home countries facilitate technology diffusion from world technological leaders to developing countries. The aspect of immigrant link we focus on is knowledge spillover through various programs of international exchange to draw upon the expertise of the individuals who have migrated—a type of externality effect on the home country. In our model, we distinguish between public technology and private technology, both of which differ across countries. The size of the talent pool in each country determines the number of skilled workers and indigenous technology levels. The consequent gap in talent wage results in a flow of talent from South to North. We show, however, that when the externality effect is sufficiently strong, there is a phase of growth during which a reverse brain drain naturally occurs. Our model’s prediction is consistent with the experience of Taiwan, which saw a reverse flow of talented people during the 1970s onwards after losing them in the 1950s and 1960s.